Metodologías activas para optimizar el proceso de enseñanza-aprendizaje en los estudiantes de la escuela de educación básica IV Centenario n°. 2, sección vespertina, Loja, 2014-2015 - Macas Gonzalez, Maria Leonor (2016)
The active methodologies are strategies used in the process of teaching and learning, in which the teacher assertively involves students become the protagonists of their own learning, meaning the same as constructive and unreceptive steps, however in most centers still remains the use of traditional methodologies characterized by memorization, repetition and teaching dogmatization; therefore it was decided to conduct this research, with the general objective to develop a teacher training program, based on the use of active methodologies, in order to optimize the process of teaching and learning. This research had a descriptive, transversal and pre-experimental type, the methods used were analytical, synthetic, deductive, inductive, historical, logical, diagnostic and statistical modeling. The pilot was conducted with 40 students chosen at random from the entire center for diagnosis, pre-test and post-test survey (using active methodologies) of my authorship was applied to a sample of 14 teachers. The results of the research allowed to determine that through the use of active methodologies can optimize the teaching-learning process.